SYNTHESIS OF IRON DISULFIDE (FES2) NANOPARTICLES COATING POLYVINYLPYRROLIDONE VIA HOT-INJECTION METHOD - HANIFAH HARUDINI PRIAMBUDI (NIM : 10214048),
Iron disulfide or FeS2 is a non-toxic, low cost, and abundant material. These properties and their high theoritical capacity make FeS2 a promising cathode material for lithium battery. However, limited reversibility as the result of large volume fluctuations, poor ionic conductivity of lithiation product, and formation of lithium polysulfides that dissolve in electrolyte makes FeS2 difficult to use as a cathode material for secondary lithium battery. Decreasing the particle size into nano-order is known to overcome these problems. Therefore in this study, synthesis of FeS2-PVP was carried out through hot-injection method. The effect of reaction time, amount of PVP, and precursor concentration on FeS2 particle size was observed. The resulting samples were characterized by X-Ray Diffractometer (XRD), UV-Vis spectrometer, Fourier Transform Infrared spectrometer (FTIR), Scanning Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM). Samples of FeS2 without impurities are obtained by using Fe:S ratio to 1:4. Reduction in the size of FeS2 particles along with reduction of reaction time, addition of PVP, and reduction of precursor concentration were expected from the visual, UV-Vis absorbance, band gap, and SEM images. We obtained FeS2-PVP particles with the size of 5,51 nm from the optimum conditions.